Horsing around: Escherichia coli ST1250 of equine origin harbouring epidemic IncHI1/ST9 plasmid with bla CTX-M-1 and an operon for short-chain fructooligosaccharides metabolism - Valcek, Adam; Sismova, Petra; Nesporova, Kristina; Overballe-Petersen, Søren; Bitar, Ibrahim; Jamborova, Ivana; Kant, Arie; Hrabak, Jaroslav; Wagenaar, Jaap A; Madec, Jean-Yves; Damborg, Peter; van Duijkeren, Engeline; et al. (Antimicrobial agents and chemotherapy, 2023)
The relatedness of the equine-associated Escherichia coli ST1250 and its single- and double-locus variants (ST1250-SLV/DLV), obtained from horses in Europe, was studied by comparative genome analysis. A total of 54 isolates of E. coli ST1250 and ST1250-SLV/DLV from healthy and hospitalized horses across Europe [Czech Republic (n=23), the Netherlands (n=18), Germany (n=9), Denmark (n=3) and France (n=1)] from 2008-2017 were subjected to whole-genome sequencing. An additional 25 draft genome assemblies of E. coli ST1250 and ST1250-SLV/DLV were obtained from the public databases. The isolates were compared for genomic features, virulence genes, clade structure and plasmid content. The complete nucleotide sequences of eight IncHI1/ST9 and one IncHI1/ST2 plasmids were obtained using long-read sequencing by PacBio or MinION. In the collection of 79 isolates, only 10 were phylogenetically close (<8 SNP). The majority of isolates belonged to phylogroup B1 (73/79, 92.4%) and carried bla CTX-M-1 (58/79, 73.4%). The plasmid content of the isolates was dominated by IncHI1 of ST9 (56/62, 90.3%) and ST2 (6/62, 9.7%), while 84.5% (49/58) bla CTX-M-1 genes were associated with presence of IncHI1 replicon of ST9 and 6.9% (4/58) with IncHI1 replicon of ST2 within the corresponding isolates. The operon for the utilization of short chain fructooligosaccharides (fos operon) was present in 55 (55/79, 69.6%) isolates, and all of these carried IncHI1/ST9 plasmids. The eight complete IncHI1/ST9 plasmid sequences showed the presence of bla CTX-M-1 and the fos operon within the same molecule. Sequences of IncHI1/ST9 plasmids were highly conserved (>98% similarity) regardless of country of origin and varied only in the structure and integration site of MDR region. E. coli ST1250 and ST1250-SLV/DLV are phylogenetically-diverse strains associated with horses. A strong linkage of E. coli ST1250 with epidemic multi-drug resistance plasmid lineage IncHI1/ST9 carrying bla CTX-M-1 and the fos operon was identified.